Combined Burst Wave Lithotripsy and Ultrasonic Propulsion for Improved Urinary Stone Fragmentation - Zwaschka, Theresa A. (J Endourol, 2018)
Purpose: Burst wave lithotripsy (BWL) is a new technology in development to fragment urinary stones. Ultrasonic propulsion (UP) is a separate technology under investigation for displacing stones. We measure the effect of propulsion pulses on stone fragmentation from BWL. Materials and Methods: Two artificial stone models (crystalline calcite, BegoStone plaster) and human calcium oxalate monohydrate (COM) stones measuring 5 to 8 mm were subjected to ultrasound exposures in a polyvinyl chloride tissue phantom within a water bath. Stones were exposed to BWL with and without propulsion pulses interleaved for set time intervals depending on stone type. Fragmentation was measured as a fraction of the initial stone mass fragmented to pieces smaller than 2 mm. Results: BegoStone model comminution improved from 6% to 35% (p < 0.001) between BWL and BWL with interleaved propulsion in a 10-minute exposure. Propulsion alone did not fragment stones, whereas addition of propulsion after BWL slightly improved BegoStone model comminution from 6% to 11% (p < 0.001). BegoStone model fragmentation increased with rate of propulsion pulses. Calcite stone fragmentation improved from 24% to 39% in 5 minutes (p = 0.047) and COM stones improved from 17% to 36% (p = 0.01) with interleaved propulsion. Conclusions: BWL with UP improved stone fragmentation compared with BWL alone in vitro. The improvement was greatest when propulsion pulses are interleaved with BWL treatment and when propulsion pulses are applied at a higher rate. Thus, UP may be a useful adjunct to enhance fragmentation in lithotripsy in vivo.